Kemampuan Pedagogik Guru Dalam Memberikan Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Didi Maksudi (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
Pedagogical competence is one of the four main competencies that are very important for a teacher or educator, this competence relates to the ability of a teacher to plan, implement and evaluate the learning process. This includes an understanding of various teaching methods, learning strategies, assessment and the ability to communicate and interact with students. This research is a field research using descriptive method with qualitative approach. Data collection through observation, interviews, and documentation, then the data is analyzed through descriptive. The result of this study is that PAI teachers at SMPN 1 Cibadak are quite good at mastering pedagogical skills. As in the formulation of the problem in this thesis is how the pedagogical ability of PAI teachers at SMPN 1 Cibadak? How is student learning motivation in PAI subjects in Class VIII I at SMPN 1 Cibadak? Can the pedagogical ability of PAI teachers increase student learning motivation? From the results of the study it was found that the PAI teacher's ability was good enough, the teacher already had insight into education, curriculum development, lesson planning, lesson implementation, and understanding of students, and evaluation of learning outcomes. Motivation to learn students at SMPN 1 Cibadak researchers took samples in class VIII I, that there are some children who are enthusiastic in learning, active in class or outside the classroom, such as participating in extracurricular activities, and there are still students who are still lazy in learning, less active, and do not participate in extracurricular activities. In the results of data analysis, it can be concluded that the learning motivation possessed by students is quite good in Islamic religious education subjects. In addition, teachers also have sufficient knowledge and experience, and students can follow the teaching and learning process in class well.